Biological Chitin–MOF Composites with Hierarchical Pore Systems for Air‐Filtration Applications. Issue 43 (28th August 2015) - Wisser, Dorothea; Wisser, Florian M.; Raschke, Silvia; Klein, Nicole; Leistner, Matthias; Grothe, Julia; Brunner, Eike; Kaskel, Stefan
Abstract Metal–organic frameworks (MOFs) are promising materials for gas‐separation and air‐filtration applications. However, for these applications, MOF crystallites need to be incorporated in robust and manageable support materials. We used chitin‐based networks from a marine sponge as a non‐toxic, biodegradable, and low‐weight support material for MOF deposition. The structural properties of the material favor predominant nucleation of the MOF crystallites at the inside of the hollow fibers. This composite has a hierarchical pore system with surface areas up to 800 m2 g−1 and pore volumes of 3.6 cm3 g−1, allowing good transport kinetics and a very high loading of the active material. Ammonia break‐through experiments highlight the accessibility of the MOF crystallites and the adsorption potential of the composite indicating their high potential for filtration applications for toxic industrial gases.